THE IMPACT OF SALES PROMOTION, CONTENT MARKETING, AND SHOPPING LIFESTYLE ON IMPULSE BUYING DECISIONS FOR BEEF PRODUCTS IN E-COMMERCE: A STUDY OF URBAN CONSUMERS - WIDIARTA, I P. G. D.; C., QAMARA; ., SUHARDI; M. H., WIJAKESUMA; A., WIBOWO (MAJALAH ILMIAH PETERNAKAN, 2025)
E-commerce has revolutionized the way consumers shop, especially in urban areas, transforming purchasing behaviors for essential commodities like beef. This study examines the impact of sales promotion, content marke- ting, and shopping lifestyle on impulse buying decisions for beef products among urban consumers in East Kali- mantan, Indonesia. Using a quantitative approach with a causal-comparative design, data were collected from 300 respondents through online surveys and analyzed using Structural Equation Modeling (SEM). The results indicate that content marketing has the most substantial influence on impulse buying decisions, as engaging and emoti- onally resonant content fosters consumer interest and drives unplanned purchases. Sales promotion, including discounts, coupons, and time-limited offers, is the second most influential factor, creating urgency and increasing perceived value. A shopping lifestyle, characterized by preferences for convenience and efficiency, also significantly affects impulse buying, though its impact is comparatively weaker. These findings underscore the importance of integrating compelling content with strategic promotional efforts to optimize consumer engagement and stimulate impulsive purchasing behavior. This research provides valuable insights for e-commerce businesses to enhance their marketing strategies and adapt to the evolving preferences of urban consumers in emerging markets like In- donesia, contributing to improved competitiveness in the digital economy.